H2‐Free Re‐Based Catalytic Dehydroxylation of Aldaric Acid to Muconic and Adipic Acid Esters. Issue 3 (10th November 2020) - Hočevar, Brigita; Prašnikar, Anže; Huš, Matej; Grilc, Miha; Likozar, Blaž
Abstract: As one of the most demanded dicarboxylic acids, adipic acid can be directly produced from renewable sources. Hexoses from (hemi)cellulose are oxidized to aldaric acids and subsequently catalytically dehydroxylated. Hitherto performed homogeneously, we present the first heterogeneous catalytic process for converting an aldaric acid into muconic and adipic acid. The contribution of leached Re from the solid pre‐reduced catalyst was also investigated with hot‐filtration test and found to be inactive for dehydroxylation. Corrosive or hazardous (HBr/H2 ) reagents are avoided and simple alcohols and solid Re/C catalysts in an inert atmosphere are used. At 120 °C, the carboxylic groups are protected by esterification, which prevents lactonization in the absence of water or acidic sites. Dehydroxylation and partial hydrogenation yield monohexenoates (93 %). For complete hydrogenation to adipate, a 16 % higher activation barrier necessitates higher temperatures. Abstract : In the present work, the conversion of bio‐based aldaric acids into muconic and adipic acid through a heterogeneous catalytic process, in the absence of corrosive reagents or gaseous H2 is reported. The mechanism of the selective removal of adjacent OH* groups on Re/C catalysts and the role of (m)ethanol in carboxylic group protection and hydrogen transfer in a slurry reactor are elucidated by DFT calculations and XPS, chemisorption, and HR‐TEM.